2016
DOI: 10.1007/s00268-015-3396-7
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy Causes Ultrasound Evidence of Increased Hepatic Steatosis

Abstract: Hepatic steatosis significantly developed 3 months after cholecystectomy. Therefore, cholecystectomy might be considered a risk factor for hepatic steatosis, but the relationship should be confirmed with long-term follow-up from a large group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
3
20
0
2
Order By: Relevance
“…Multivariate logistic regression analysis showed that cholecystectomy was significantly associated with an increased risk of MetS (OR = 1.872, 95% CI: 1.193‐2.937) whereas gallstone disease was not (OR = 1.267, 95% CI: 0.901‐1.782) . In accordance with the above findings, several epidemiological studies have also shown that cholecystectomy is usually more closely, or even solely, associated with MetS components than gallstone disease when the two conditions are studied separately (Table ). The results of the above studies give added weight to the emerging concept of the GB as an organ that plays a significant role in systemic metabolism.…”
Section: Metabolic Consequences Of Cholecystectomysupporting
confidence: 66%
See 1 more Smart Citation
“…Multivariate logistic regression analysis showed that cholecystectomy was significantly associated with an increased risk of MetS (OR = 1.872, 95% CI: 1.193‐2.937) whereas gallstone disease was not (OR = 1.267, 95% CI: 0.901‐1.782) . In accordance with the above findings, several epidemiological studies have also shown that cholecystectomy is usually more closely, or even solely, associated with MetS components than gallstone disease when the two conditions are studied separately (Table ). The results of the above studies give added weight to the emerging concept of the GB as an organ that plays a significant role in systemic metabolism.…”
Section: Metabolic Consequences Of Cholecystectomysupporting
confidence: 66%
“…GB removal can facilitate the development of non‐alcoholic fatty liver disease (NAFLD), a hepatic manifestation of MetS. In a recent study, Yun S et al found a significant development in hepatic steatosis in patients 3 months after cholecystectomy . Using data from US adults in the Third National Health and Nutrition Examination Survey (NHANES III), Ruhl et al also showed that cholecystectomied subjects had a higher prevalence of NAFLD (48.4%) than those with gallstones (34.4%) or without gallstone disease (17.9%).…”
Section: Metabolic Consequences Of Cholecystectomymentioning
confidence: 96%
“…Their conclusion supports the results of another study that showed a significant increase in the development of hepatic steatosis at 3 months after cholecystectomy, regardless of whether heavy drinking occurred. 34 In accordance with the above findings, a US cohort study based on the NHANES III showed that NAFLD, a hepatic manifestation of MetS, was associated with cholecystectomy, but not gallstones, even after controlling for multiple factors common to both disorders. 6 This association was stronger in men than in women, as 68% of the cholecystectomized men had NAFLD.…”
Section: Cholecystectomy and Mets Componentsmentioning
confidence: 54%
“…In this framework, cholecystectomy significantly deprives the body from a number of gallbladder functions acting as concentrating and pacing organ, with paramount 'endocrine' consequences during fasting and postprandially. Disrupted concentration, blunted transintestinal flow, and fast enterohepatic re-circulation of BAs acting as signaling molecules, 26 will ultimately interfere with gene expression of BAs/FXR, and BA/GPBAR-1 axes. 25 A missing gallbladder will also impoverish the circulating levels of FGF19, 27 and eliminate the gallbladder GPBAR-1.…”
mentioning
confidence: 99%